2019
DOI: 10.1177/1129729819888423
|View full text |Cite
|
Sign up to set email alerts
|

The impact of flushing with pre-filled saline syringes on the incidence of peripheral venous catheter failure: A quasi-experimental study

Abstract: Background: Short peripheral venous catheters are one of the most frequently used devices in hospitals. Peripheral venous catheter failure, defined as the unscheduled dysfunction of peripheral venous catheter, is common and frequently entails a new invasive procedure. Flushing the catheter maintains patency and could prolong peripheral venous catheter dwell time. The introduction of pre-filled saline flushing syringes as compared to manually filled saline flushing syringes could facilitate the frequency of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…unit of measurement, lack of core outcome definitions, heterogeneity). A recent pre-and post-test study observed a decrease in PIVC failure associated with the use of pre-filled syringes [28]. However, the overall failure rate even post-intervention remained high (43%) indicating that there are other drivers at play related to PIVC failure.…”
Section: Discussionmentioning
confidence: 98%
“…unit of measurement, lack of core outcome definitions, heterogeneity). A recent pre-and post-test study observed a decrease in PIVC failure associated with the use of pre-filled syringes [28]. However, the overall failure rate even post-intervention remained high (43%) indicating that there are other drivers at play related to PIVC failure.…”
Section: Discussionmentioning
confidence: 98%
“…In two studies included in this review, the use of pre-filled syringes significantly reduced PVC failures and complication occurrence, increased the length of dwell of this device and reduced related costs (27,29) . It is pointed out that pre-filled syringes are marketed in order to minimize the incorrect choice of syringe size and solution to be used.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PVC, the volume and interval during flushing did not interfere in obstruction occurrence, on the other hand, the greater number of PVC manipulations throughout the day was a predictor of its failure (S1 (18) ); negligence or irregular performance of flushing generated an advanced stage of phlebitis in patients using PVC (S5 (22) ); flushing preparation with pre-filled syringes significantly reduced obstruction occurrence, with increased catheter dwell time and related costs reduction (S10 (27) ; S12 (29) ).…”
Section: ) Flushing -Volume Regimen Solution Preparation and Techniqu...mentioning
confidence: 99%
“…According to the study findings, nurses draw the required flushing volume from a 1000 mL bag of normal saline that is used throughout each shift. Manually prepared syringes are subjected to more manipulation during the filling procedure, putting them in closer touch with the healthcare staff and increasing the risk of catheter contamination [ 53 ]. Previous studies conducted in Portugal indicate that adherence to PIVC flushing is often overlooked by professionals due to a lack of recent training in vascular access, a lack of material for flushing, or user-unfriendly storerooms [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%